Investigation of hardness of drinking water according to the parameters of admittance - Pokhodylo, Ye. V.; Martynovych, N. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
It is suggested to control hardness of drinking water for the parameters of the complex conductivity (admittance), two-pole device, by which it is supplied in electric circuit of AC. The dependence of active and reactive components of the admittance of the concentration of individual components in the water, particularly calcium, magnesium and iron is investigated in the paper.